MEDAN MAKNA VERBA MEMUKUL DALAM BAHASA DAYAK KANAYATN ISOLEK BAJARE - Muriati, Eka; Madeten, Sisilya Saman; Patriantoro, Patriantoro (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractSemantic field verbs hit that contained in Dayak Language Kanayatn Bajare Isolect has different types and functions. This research problem, to know the component of meaning, kind of meaning and meaning, and semantic function of verbs hit in Dayak Kanayatn Bajare Isolect. This research focuses on the semantic field, with the aim of (1) describing the components of the meaning language of Kanayatn Bajare Isolect; (2) describing the type and meaning of the verb striking in the Dayak language of Kanayatn Bajare Isolect; and (3) describing the function of semantic verbs hit in Dayak language Kanayatn Bajare Isolect. Based on the results of research that has been done, it was found that in Dayak Kanayatn Bajare Isolect there are 20 lexeme verbs hit without tools, and 3 lexeme verbs hit without tools and using tools. The types of meanings and meanings found in lexical meanings, 41 cultural meanings, 39 grammatical meanings, and 41 semantic function.Keywords: semantics, meaning fields, verbs, hit, Bajare Isolect